A Decision Support System For Determining Photography Vendors In The City Of Semarang Using The Hybrid SAW Method In A Multi Attribute Topsis: Sistem Pendukung Keputusan Penentuan Vendor Fotografi Di Kota Semarang Menggunakan Metode Hybrid SAW Dalam Topsis Multi Attribute - Afrian Putra, Viki; Untari N, Dewi Handayani (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
AbstractWedding photography vendors are used as one of the most important things in capturing a moment of happiness felt by the newlywed couple, the families of both parties and their closest relatives who were present to enliven the wedding ceremony that was held. The many types of vendors offering their services make it difficult for prospective clients to determine the type of vendor that suits the client's wishes. This is a major problem for prospective clients in finding photography vendors that suit their budget and desires. Apart from that, prospective clients also do not know how many types of photography vendors are available in that city. To overcome this, a system is needed using the SAW and TOPSIS methods. The purpose of this research is. The purpose of this research is to find out the results of implementing the SAW and TOPSIS methods in the support system for determining the type of photography vendor in Semarang City. The system development method used is waterfall. As a result of implementing these two methods, the system created has met expectations to be able to assist in providing recommendations for photography vendors. From the results of black box testing, it can be concluded that the system has succeeded in producing recommendations for photography vendors in Semarang City and meets functional needs.